2021
DOI: 10.1002/smtd.202100736
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Design for Electrochemical Reduction of CO2 to Multicarbon Products

Abstract: solve this problem with electricity converted from renewable energies (such as solar and wind energy) to transform CO 2 into fuels and industrial raw materials. From the thermodynamic view, there are many potential products that could be obtained from CO 2 RR, such as CO, CH 4 , C 2 H 4 , HCOOH, and C 2 H 5 OH. Meanwhile, hydrogen evolution reaction (HER) is always competing with CO 2 RR in aqueous solutions, usually potassium bicarbonate solutions. Possible CO 2 RR paths are listed in Figure 1 : [4][5][6][7][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 116 publications
(199 reference statements)
1
50
0
Order By: Relevance
“…In addition to facet orientations, defects and grain boundaries of Cu have been widely explored, showing remarkable impacts on the production of C 2 + fuels by tuning the surface binding energy and altering the reaction pathway. [44][45][46] Cuenya and coworkers synthesized a prism-shaped Cu electrode via a facile strategy to obtain a higher ethylene current density. It was observed that the high density of defect sites greatly enhanced the selectivity of ethylene via stabilizing the key intermediates.…”
Section: Defects and Grain Boundariesmentioning
confidence: 99%
“…In addition to facet orientations, defects and grain boundaries of Cu have been widely explored, showing remarkable impacts on the production of C 2 + fuels by tuning the surface binding energy and altering the reaction pathway. [44][45][46] Cuenya and coworkers synthesized a prism-shaped Cu electrode via a facile strategy to obtain a higher ethylene current density. It was observed that the high density of defect sites greatly enhanced the selectivity of ethylene via stabilizing the key intermediates.…”
Section: Defects and Grain Boundariesmentioning
confidence: 99%
“…Due to its unique ability to catalyze CO 2 ER toward a number of hydrocarbons, aldehydes, and alcohols requiring more than two electron transfers with substantial Faradaic efficiencies (FE), Cu has been overall recognized as the gold standard among pure metal catalysts since 1985. …”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms of CO 2 and N 2 reduction are still not conclusive, numerous studies have shown that defects and heteroatom dopants (e.g., N, B, P) can modify the band gap, charge distribution, and spin density of graphene and thereby boost the catalytic activity and selectivity toward CO 2 and N 2 reductions. [122][123][124][125][126][127] Graphene-supported metal nanoparticles and single-atom catalysts have also been proven as promising electrocatalysts for CO 2 and N 2 reductions. [128][129][130][131][132] Given the flexibility to tailor the topological defects and chemical dopants and to host nanoparticulate and single-atom metal catalysts, the 3D continuously porous graphene shows great promise for applications in electrochemical CO 2 and N 2 reductions with rationally optimized performance.…”
Section: Electrochemical Co 2 Reduction and N 2 Reductionmentioning
confidence: 99%